2021
DOI: 10.35741/issn.0258-2724.56.5.49
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Mathematical Modeling on Conceptual Understanding Among Student-Teachers

Abstract: The present study investigates the effect of mathematical modeling on conceptual understanding among student-teachers. Also, the study proposes relevant materials and activities in mathematical modeling. Two classes of 140 student-teachers participated in the study. Mathematical modeling instruction was used in the treatment group, while the comparison group was taught by a teacher-centered method. T-Test results showed a difference between the treatment and comparison groups in terms of conceptual understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In line with the claim made by Goodsett and Schmillen [25] that teachers with a high level of critical thinking would be skilled at mathematical modelling, pre-service teachers in this study showed a significant relationship between critical thinking and modelling competency (RO4). This assertion is supported by the research [26], which found that students' ability to work independently was influenced by how their critical thinking skills evolved while creating mathematical models. Introducing critical thinking early in a student's higher education experience aids in their understanding of critical thinking, enhances their skills in mathematical modelling competency, and promotes a structured and fair approach to these vital concepts.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In line with the claim made by Goodsett and Schmillen [25] that teachers with a high level of critical thinking would be skilled at mathematical modelling, pre-service teachers in this study showed a significant relationship between critical thinking and modelling competency (RO4). This assertion is supported by the research [26], which found that students' ability to work independently was influenced by how their critical thinking skills evolved while creating mathematical models. Introducing critical thinking early in a student's higher education experience aids in their understanding of critical thinking, enhances their skills in mathematical modelling competency, and promotes a structured and fair approach to these vital concepts.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, it ensures a structured and fair approach to these essential concepts, promoting equity among students [25]. The findings of the study indicate that student's capacity for independent work was affected by the manner in which their critical thinking skills developed while they were developing mathematical models [26].…”
Section: B the Correlation Between Critical Thinking And Mathematical...mentioning
confidence: 91%
See 1 more Smart Citation
“…When working on math problems about SPLDV (Two-Variable Linear Equation System), students often get it wrong; such as not answering the question completely as to what the problems contained in the question and wrong in making mathematical modeling in problems (Rahayuningsih & Qohar, 2014). Mathematical modeling is a concept of mathematical problems to be able to solve problems correctly, therefor it is useful for developing the understanding of students' thought (Salha & Qatanani, 2021).…”
Section: Analysis Of Question Numbermentioning
confidence: 99%